Rising to the challenge: Entrepreneurship ecosystems and SDG success. Issue 3 (1st October 2020) - Liguori, Eric; Bendickson, Joshua S.
ABSTRACT: Most government entities are focused on how they can accomplish two big goals: (a) stimulating their economies and (b) moving the needle in solving the United Nations Sustainable Development Goals. This article explores the role of the entrepreneurial ecosystem as a key means by which both of these goals, social and economic, can be influenced for the better. Specifically, we offer five best practices for cultivating successful entrepreneurial ecosystems, and call on policy makers and entrepreneurs alike to continue to work together to help improve economies, create jobs, and solve some of the world's biggest problems.